Prevalence and correlates of metabolic syndrome in patients with initial-treatment and drug-naïve bipolar disorder: A large sample cross-sectional study - Yilin Fang; Bingchuan Yan; Zhihua Liu; Lin Zhang (PLoS ONE, 2025)
Patients with bipolar disorder (BD) are frequently prone to metabolic syndrome (MetS), and their co-morbidity adversely affects patient care outcomes. This study aimed to determine the prevalence of MetS and its clinical correlates among initial-treatment and drug-naïve (ITDN) BD patients.We recruited a cohort of 841 ITDN BD patients. Socio-demographic and clinical data were collected, and patients underwent routine serological testing, which included fasting blood glucose, lipid profiles, thyroid function, and prolactin levels. Psychometric evaluations were also conducted to measure manic, depressive, and psychotic symptoms, as well as illness severity. Additionally, we utilized a transformation approach for continuous variable analysis to compute a MetS score.We found a MetS prevalence of 17.84% among the study participants. Binary logistic regression identified age, body mass index (BMI), low-density lipoprotein cholesterol (LDL-C), free tetraiodothyronine (FT4), and psychotic symptoms as significant predictors of MetS development. Further, multiple linear regression analysis indicated that advanced age was a significant predictor of higher MetS scores.The findings highlight the prevalence of MetS in ITDN BD patients and suggest that certain demographic and clinical factors are influential in the development and severity of MetS. These insights may guide the development of targeted preventive and therapeutic strategies for MetS in this patient population.